Application of Cyanobacteria (Roholtiella sp.) Liquid Extract for the Alleviation of Salt Stress in Bell Pepper (Capsicum annuum L.) Plants Grown in a Soilless System - Adewale Suraj Bello (18891643) (2021)
Salinity is one of the abiotic stresses that affect crop growth and productivity in arid and semi-arid regions. Unfortunately, there are few known methods to mitigate the deleterious impacts of salt stress on the development and yield of vegetable crops. Blue-green algae (cyanobacteria) are endowed with the potential to curb the negative impacts of salt stress as they are characterized by biostimulant properties. The present work aimed to investigate the effects of Roholtiella sp. as a foliar extract on the growth characteristics, physiological and biochemical responses of bell pepper (Capsicum annuum L.) plants under varying levels of salinity conditions. A soilless water experiment was carried out in a greenhouse where bell pepper seedlings were grown under five salt concentrations (0, 50, 200, 150, and 200 mM of NaCl). Growth characteristics, pigments content, relative water content, and antioxidant activity (CAT) were determined. Our results showed that growth parameters, relative water content (RWC), chlorophyll a & b concentrations under salinity conditions were negatively affected at the highest concentration (200 mM). Interestingly, the application of Roholtiella sp. foliar extract enhanced the plant growth characteristics as shoot length increased by 17.014%, fresh weight by 39.15%, dry and weight by 31.02%, at various salt treatments. Moreover, chlorophyll a and b increased significantly compared with seedlings sprayed with water. Similarly, RWC exhibited a significant increase (92.05%) compared with plants sprayed with water. In addition, antioxidants activities and accumulation of proline were improved in Roholtella sp. extract foliar sprayed seedlings compared to the plants foliar sprayed with water. Conclusively, at the expiration of our study, the Rohotiella sp. extract-treated plants were found to be more efficient in mitigating the deleterious effects caused by the salinity conditions which is an indication of an enhancement potential of tolerating salt-stressed plants when compared to the control group. Other Information Published in: Plants License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/plants11010104